HETERONOMIA E RESISTÊNCIA: POROSIDADE E EXTERIOR EM CERTA POESIA BRASILEIRA (Muitas Vozes, 2024)
Based on Florencia Garramuño's idea of heteronomy, this article analyses some contemporary brazilian poems and poets. According to my hipothesis, many of the latter make use of devices that underline poetry as a permeable kind of speech, depicting its (non-)identity not through a discourse of specificity or particularity. In doing so, part of brazilian contemporary poetry places itself in an expanded field that 1) abdicates any transcendence regarding other kinds of discoursive production in the social field and 2) reconceptualize the ideia of social critique, that henceforth cannot be legitimized from an exterior/transcendent position. Finally, in order to clarify such problems, I compare Garramuño's paradigm to Iumna Simon's understanding of the possible relations between literatura and politics.